The performance effects of innovative service transition strategies - Christoph Buck; Nils-Ole Floegel; Maximilian B. Stöter; Kevin C. Desouza; Timothy Robb (Journal of Innovation & Knowledge (JIK), 2025)
In recent years, the management research has increasingly discussed service transition. However, studies have not used sufficiently granular empirical data for valid quantitative evaluation of service-intensive strategies by, for example, examining the possible effects of resource slack on firm performance. To test the hypothesis that resource slack moderates the performance effects of a servitization-based strategy, a regression model was applied to data spanning several industrial and geographic sectors. Tobin's q and return on assets were applied as uniform measures of financial performance. The study shows some potential positive and negative effects of the servitization of manufacturing firms on their financial performance. However, resource slack on its own is not shown to moderate these effects. The conclusion is that servitization is not a panacea for manufacturing firms, nor is the combination of servitization with resource slack. The contribution of this article lies in providing further evidence of the positive performance effects of servitization, while showing that servitization can have negative effects on firm performance in certain circumstances.
Keywords: O33; L60; 650; Service transition; Servitization; Corporate performance; Service ratio; Diversification strategy